X-ray diffraction analysis of KY3F10 nanoparticles doped with Nd and preliminary studies for its use in high-dose radiation dosimetry - Rodrigo Uchida Ichikawa; Horacio Marconi da Silva Matias Dantas Linhares; Andre Santos Barros Silva; Maria Ines Teixeira; Izilda Marcia Ranieri; Xavier Turrillas; Luis Gallego Martinez (Brazilian Journal of Radiation Sciences)
In this work, the structure and microstructure of Nd:KY3F10 nanoparticles was probed using X-ray synchrotron diffraction analysis. Rietveld refinement was applied to obtain cell parameters, atomic positions and atomic displacement factors to be compared with the ones found in literature. X-ray line profile methods were applied to determine mean crystallite size and crystallite size distribution. Thermoluminescent (TL) emission curves were measured for different radiation doses, from 0.10 kGy up to 10.0 kGy. Dose-response curves were obtained by area integration beneath the peaks from TL. The reproducibility of the results in this work has shown that this material can be considered a good dosimetric material.